2020
DOI: 10.1038/s41598-020-76595-0
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of asymptomatic leptospirosis among urban sanitation workers from Kota Kinabalu, Sabah, Malaysian Borneo

Abstract: Leptospirosis is a public health challenge in Sabah State of Malaysian Borneo. Rapid urbanization, rural-to-urban migration, and undocumented immigration in Sabah have increased the pressure on the urban garbage disposal system. Rodents and other small animals thrive under these conditions. We hypothesized that urban sanitation workers would be at risk of developing leptospirosis. In total, 303 urban sanitation workers with a mean age of 42.6 years were enrolled in this study. The serum samples collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…( 54 ). In addition, they had the possibility of having Helicobacter pylori infections ( 55 ); leptospirosis ( 56 ); intestinal parasites; soil-based transmitted helminthes ( 57 ); arthralgia as the most prominent symptom ( 58 ); and also GI problems ( 59 ). The majority of these studies concluded that sanitary workers who had food and drink while they were working and who did not have personal protective equipment had the possibility of having gastroenteritis problems.…”
Section: Discussionmentioning
confidence: 99%
“…( 54 ). In addition, they had the possibility of having Helicobacter pylori infections ( 55 ); leptospirosis ( 56 ); intestinal parasites; soil-based transmitted helminthes ( 57 ); arthralgia as the most prominent symptom ( 58 ); and also GI problems ( 59 ). The majority of these studies concluded that sanitary workers who had food and drink while they were working and who did not have personal protective equipment had the possibility of having gastroenteritis problems.…”
Section: Discussionmentioning
confidence: 99%
“…Most infections also occurred in high poverty areas within each New York Borough and predominantly among men. This increasing trend of Leptospirosis in urban environments could be attributed to poor socioeconomic status [17] unsanitary waste handling and worsening rodent infestation [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars studied troph erymaw hipplei (Schoniger-Hekeleetal, 2007); Anti-HAV Antibodies (Toseva et al, 2018). In addition, they exposed with leptospirosis (Jeffree et al 2020); majority of them had sero positivity to Hepatitis (Levin et al, 2000); seropositivity to hepatitis A virus (Divizia et al, 2008).…”
Section: Occupational Related Gastrointestinal Conditionsmentioning
confidence: 99%